If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-4)+6=7x-9-5x
We move all terms to the left:
3(x-4)+6-(7x-9-5x)=0
We add all the numbers together, and all the variables
3(x-4)-(2x-9)+6=0
We multiply parentheses
3x-(2x-9)-12+6=0
We get rid of parentheses
3x-2x+9-12+6=0
We add all the numbers together, and all the variables
x+3=0
We move all terms containing x to the left, all other terms to the right
x=-3
| 18x=8x-20 | | 13s-5=-11+12s | | 4x+9+6x-23+40=180 | | 79=7w+3(4w–1) | | Y=3.5x+22 | | 31x=45 | | –9+2z=–7z | | u/5-8=9 | | 15b=17+14b | | -5+3x+8=2x+9 | | 5x2/5=0 | | -11+17m=16m | | 7x-14-10=20x-8x | | +2y–18+8y=–2 | | x31=45 | | 20-14n=-12n-8 | | 3x+85=119 | | 4x+21=x-28 | | d−8=≥35 | | 8(p-6)=48 | | 11=35-a | | A(x)=(x)(150-2x) | | 2y–18+8y=–2 | | 1.8·(u÷1.8)=3.6 | | f/0.25*0.25=16*0.25 | | 2x+3+5=20 | | -(v+6)+2(4v+2)=45 | | 13=w-12÷2 | | 6a+23+3a+31=180 | | 5g−7=−3g+1 | | y/25-4y=9y-1y= | | 5^x=50000 |